A Comparative Analysis of the Practice and Legal Reference of Wasiat Wajibah Indonesia and Malaysia - Naqiyyatussa'diyah, Naqiyyatussa'diyah; Jamilah, Jamilah (IJISH (International Journal of Islamic Studies and Humanities), 2025)
This study aims to analyze the comparison of the implementation and regulations regarding mandatory wills in Indonesia and Malaysia and relate it to maslahah according to Izzudin bin Abdissalam. This research uses a qualitative approach. The data collection technique used in this research is a literature study through documentation. The object of this research is the rules and implementation of mandatory wills in Indonesia and Malaysia when connected with the maslahah of Izzudin bin Abdissalam. The results of this study indicate that first, Indonesia provides mandatory wills to adopted children or adoptive parents with a share of 1/3, by referring to Hazairin. The rule is listed in KHI article 209 because it is not binding. The designation has been expanded. At the same time, Malaysia gives to the grandchildren. The rule is listed in the Enakmen, which has a binding legal nature; however, not all states in Malaysia regulate mandatory wills, and not all mandatory will rules are the same. Secondly, if the issue of compulsory legacy is related to the maslahah of Izzudin bin Abdissalam, then it is included in the haqiqi maslahah because it provides happiness (farh) for the recipient of the compulsory bequest, and the maslahah can be known directly by the intellect and is classified as a worldly maslahah.